Toxin-producing Escherichia coli: a long-term retrospective study in dogs and cats between 2017 and 2023 in Italy - De Luca, Giovanna; Costantini, Giorgia; Borrelli, Luca; Izzo, Pasquale; Riccone, Nunzia; Del Piano, Francesca; Valvini, Ornella; Gallo, Amalia; Auriemma, Clementina; Alfano, Flora; Paone, Marco; Sgroi, Giovanni; et al. (Frontiers in Veterinary Science, 2025)
IntroductionToxin-producing Escherichia coli are gastrointestinal agents found in both animals and humans, potentially leading to mild-to-severe pathogenic outcomes. Therefore, this study aimed to assess the prevalence of toxin-producing E. coli in owned and stray dogs and cats in Southern Italy in order to provide insights into the epidemiology of these zoonotic bacterial infections.MethodsDuring necropsy, organ swabs (i.e., intestine, liver, lung, spleen, lymph node, and brain) from dogs and cats were collected and analyzed to isolate E. coli colonies through bacterial culture between 2017 and 2023. The isolated strains were then subjected to biomolecular investigation for pathogenicity factors.ResultsOut of 911 animals, 451 (49.5%) tested positive for E. coli, including 252 (56.1%) dogs and 199 (43.1%) cats. The higher prevalence among dogs was statistical significant (p < 0.01) and associated with a higher risk of infection (OR = 1.69). However, no statistically significant difference in prevalence over the years was found (p = 0.150). At least one virulence factor was detected in 22% of animals, with 12% exhibiting pathogenicity factors (CNF, CDT, LT, and ST) and 10% showing virulence genes (vtx1, vtx2, and eae). Cats were significantly more likely to produce verocytotoxin compared to dogs (p = 0.020, OR = 2.04).DiscussionThese findings suggest a wide circulation of toxin-producing E. coli in dogs and cats in Southern Italy, highlighting the importance of routine screening for these agents to ensure animal welfare and public health.